2008
DOI: 10.1016/j.drudis.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and lessons in the use of X-ray structural information in drug design

Abstract: IntroductionThe drug discovery industry has never been under such pressure to deliver as it is today. While R&D costs spiral higher, attrition statistics in clinical development show no signs of improvement and may actually be getting worse. For example, the FDA highlighted in March 2004 that a drug entering phase 1 clinical development in the year 2000 was less likely to reach the market than one that entered clinical development in 1985 [1]. It is a truism that much of the fate of a drug candidate in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
111
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 85 publications
0
111
0
4
Order By: Relevance
“…Entropic and enthalpic contributions were significant. There have been criticisms about the magnitude of ligand conformational energy changes during protein binding [32], based on errors induced by force field calculations being inadequate for calculating energies, and errors in using X-ray data which inaccurately portray conformations, distort ring structures, induce steric clashes etc [16].…”
Section: Conformational and Configurational Effects On Binding Energiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Entropic and enthalpic contributions were significant. There have been criticisms about the magnitude of ligand conformational energy changes during protein binding [32], based on errors induced by force field calculations being inadequate for calculating energies, and errors in using X-ray data which inaccurately portray conformations, distort ring structures, induce steric clashes etc [16].…”
Section: Conformational and Configurational Effects On Binding Energiesmentioning
confidence: 99%
“…However it has been shown [16] that published X-ray structures suffer from many problems, including poor fits, such that conformations and configurations (bond lengths, angles etc) can be unrealistic and highly distorted. Amides can be cis or non-planar, and even planar aromatic rings can be deformed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was reported that there was a serious concern that some low quality of X-ray crystal structures can affect the docking procedure and can mislead the development and verification of the scoring function and parameters. 36,37) …”
Section: Properties Of the Drug Candidatesmentioning
confidence: 99%
“…These include difficulties in obtaining high-quality crystals of the protein of interest (Niedzialkowska et al, 2016), crystal-packing artefacts in the structure and trapping only a static snapshot of the proteininhibitor complex (Steuber et al, 2006;Davis et al, 2008). These problems, in particular the generation of high-quality crystals, have a significant impact in the membrane-protein field.…”
Section: Introductionmentioning
confidence: 99%